MATHEMATICAL LANGUAGE AND ITS REFLECTIONS ON STUDENT LEARNING: AN EXPERIENCE IN MIDDLE SCHOOL SPEAKINGS OF THE NEW EDUCATION OF YOUTH AND ADULTS (NEJA) - Estaneck Rangel dos Santos, Elaine; Junior Cordeiro de Carvalho, Almy; Campos de Souza Amaral, Shirlena; do Rosario Silva, Gabriela (LINKSCIENCEPLACE, 2026)
In Brazil, the National Curricular Parameters (PCNEM) and the National Curricular Guidelines (DCNEM) refer to the main official documents that subsidize and guide school practices, especially in secondary education, Which express the guidelines of the proposals formulated by the official field, in order to help in the dissemination and diffusion of the educational policy produced to serve the nation, based on practices, conceptions, values and intentions of the various actors that make up the school in its multiple Spaces. Based on research data, the teaching and learning of the Mathematics curriculum component in Basic Education has been a great challenge for educators, managers and politicians in general. Within this educational panorama, the New Education for Young People and Adults (NEJA) stands out, a modality of education that is still influenced by state policies, that is, state education systems, as it is an updated Government proposal Of the State of Rio de Janeiro, which has undergone constant changes in the workload and course completion time. Reflecting on this modality of education, this research is based on the following question: how are language and mathematics teaching perceived by NEJA high school students in a public school in the municipality of Campos dos Goytacazes / RJ? It starts from the hypothesis that the teaching of Mathematics is developed as a common discipline, without due attention to its complexity and the presumed school deficit. With this in view, this is justified by the importance of understanding the limitations of the students and of curricular proposal for the learning of mathematics in the context of NEJA for high school.